Konsep Negara dan Relevansi terhadap NKRI Perspektif Emha Ainun Nadjib - Muh. Ainun Najib (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
State and power are two things that cannot be separated from one another. Substantially, both have the main purpose of creating prosperity for the people. In fact, the Indonesia's democratic system seems to be imperfect. Therefore, it needs to have reorientation and revitalization of the concept in its implementation. The thought of Muhammad Ainun Najib (Cak Nun), in this context, is an alternative offer, such as; first, there is a distinction between state institutions and government institutions, between the head of state and the head of government, for the sake of creating political stability and the administration of the good governance; second, the criteria of a leader need to have scientific quality that is not only knowing issues of the personal and group interests, but also understanding in detail about the life of the regions; third, Indonesia should have five national pillars such as people, Indonesian National Army (TNI), intellectuals, customs and culture, as well as spiritual powers. Those five pillars are supposed to support the upright and the solid state of the Republic of Indonesia.